An Updated Review of Biomimetic Materials for Restorative Dentistry (International Journal of Food and Nutritional Sciences, 2022)
Over the past decade, biomimetic materials have advanced rapidly, with novel materials entering the market. These materials attempt to preserve tooth structure, restore general health, and improve treatment predictability. This review article explores biomimetic materials used in restorative dentistry.